Risk Factors that Impact Treatment with Oral Janus Kinase Inhibitors Among Adult Patients with Atopic Dermatitis: A Nationwide Registry Study - Ida Vittrup; David Thein; Simon Francis Thomsen; Alexander Egeberg; Jacob P. Thyssen (Acta Dermato-Venereologica, 2024)
The European Medicines Agency recently limited the use of oral Janus kinase inhibitors in certain patient populations, including those with atopic dermatitis. This cross-sectional study used the Danish national registers and Danish Skin Cohort to assess the prevalence of risk factors that potentially impact choice of treatment with oral Janus kinase inhibitors in adult patients with atopic dermatitis. From the Danish national registers and Danish Skin Cohort, 18,618 and 3,573 adults with atopic dermatitis, respectively, were identified. Half of the patients (49.5%) had, at some point, been registered to have at least 1 risk factor that could impact treatment with oral Janus kinase inhibitors. Non-modifiable risk factors recorded were cancer (5.6%), major adverse cardiovascular events (2.6%), venous thromboembolism (2.0%), smoking history (15.6%), and age ≥ 65 years (12.4%). Among patients ≥ 65 years of age, the mean (standard deviation) number of risk factors were 3 (1.4), and almost half of these patients had, at some point, been registered to have 1 or more non-modifiable risk factors in addition to their age. In conclusion, risk factors that may impact treatment with oral Janus kinase inhibitors were frequent in Danish adults with atopic dermatitis, especially among older individuals. Dermatologists need support and continuously updated long-term safety data when risk-evaluating patients with atopic dermatitis prior to initiation of advanced